Effectiveness of integrated psychological therapy on clinical, neuropsychological, emotional and functional outcome in schizophrenia: a RCT study. (2nd September 2020) - Aloi, Matteo; de Filippis, Renato; Grosso Lavalle, Francesca; Chiappetta, Enrico; Viganò, Caterina; Segura-Garcia, Cristina; De Fazio, Pasquale
Abstract: Background: Cognitive impairment is considered a central feature of schizophrenia (SZ) and several rehabilitation treatments have been developed to try to improve cognitive deficits. Aims : The aim of the present study was to analyze the effectiveness of integrated psychological therapy (IPT) compared with a standard treatment (TAU) in two groups of patients with SZ, using a comprehensive testing battery of clinical, cognitive, social cognition and functional outcome domains. Methods: Forty-one patients with SZ were assigned to IPT or TAU groups in a randomized controlled trial (RCT). Psychopathological, neuropsychological, emotional and functional outcome variables were assessed at baseline and after 36 weeks of treatment. Results: The IPT group showed significant improvements than the TAU group regarding clinical and functional outcome variables. Moreover, the IPT group improved significantly in the cognitive domains and emotional functioning. Finally, linear regression has highlighted that the improvement of cognitive variables depends on having done the IPT treatment. Conclusions: IPT seems to be effective in improving clinical, neuropsychological, emotional and functional outcome in chronic SZ inpatients. Further studies would be desirable to deepen the effectiveness of IPT in the field of the psychiatric rehabilitation pointing to the possibility of recovery from mental illness.